CULTURAL DAKWAH AND MUSLIM MOVEMENTS IN THE UNITED STATES IN THE TWENTIETH AND TWENTY-FIRST CENTURIES - Mark Woodward (Aqlam: Journal of Islam and Plurality, 2020)
Abstract: There have been Muslims in what is now the United States since tens of thousands were brought as slaves in the 18th and early 19th centuries. Very few maintained their Muslim identities because the harsh conditions of slavery. Revitalization movements relying on Muslim symbolism emerged in the early 20th century. They were primarily concerned with the struggle against racism and oppression. The Moorish Science Temple of American and the Nation of Islam are the two most important of these movement. The haj was a transformative experience for Nation of Islam leaders Malcom X and Muhammad Ali. Realization that Islam is an inclusive faith that does not condone racism led both of them towards mainstream Sunni Islam and for Muhammad Ali to Sufi religious pluralism.Keywords: Nation of Islam, Moorish Science Temple, Revitalization Movement, Malcom X, Muhammad Ali. Abstract: Sejarah Islam di Amerika sudah berakar sejak abad ke 18 dan awal 19, ketika belasan ribu budak dari Afrika dibawa ke wilayah yang sekarang bernama Amerika Serikat. Sangat sedikit di antara mereka yang mempertahankan identitasnya sebagai Muslim mengingat kondisi perbudakan yang sangat kejam dan tidak memungkinkan. Di awal abad 20, muncul-lah gerakan revitalisasi Islam. Utamanya, mereka berkonsentrasi pada gerakan perlawanan terhadap rasisme dan penindasan. The Moorish Science Temple of American dan the Nation of Islam adalah dua kelompok terpenting gerakan perlawanan tersebut. Perjalanan ibadah haji memberikan pengalaman transformatif bagi pimpinan kedua kelompok gerakan tersebut, yaitu Malcom X dan Muhammad Ali. Pemahaman Islam yang inklusif yang tidak sejalan dengan rasisme mendekatkan mereka dengan ajaran-ajaran mainstream Islam sunni, dan (terutama) Muhamad Ali yang condong ke pluralisme ajaran kaum Sufi.Kata Kunci: Nation of islam, Moorish Science Temple, Gerakan revitalisasi, Malcom X, Muhammad Ali.